GeoPeer: A Location-Aware Peer-to-Peer System - Araújo, Filipe (2009)
This paper presents a novel peer-to-peer system that is particularly well suited to support context-aware computing. The system, called GeoPeer, combines the advantages of general purpose peer-to-peer systems with the suitability of geographical routing for supporting location-constrained queries and information dissemination. To achieve this goal, GeoPeer incorporates sophisticated mechanisms to establish long-range contacts that permit to achieve a small network diameter. These mechanisms take explicitly into account the unbalanced distribution of nodes in the geographical space